А ты постарайся!: рассказы и повесть / В. В. Голявкин - Голявкин Виктор Владимирович (Любимое чтение, 2008)
Экземпляры: ф. 3 (20081117) / Инвентарный номер: 92844 / Цена: 83.27 / Авт.знак: Г 63 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6